Do MCHC, MPV, and Procalcitonin Levels Determine Prognosis in Acute Coronary Syndrome? - Serhat Karaman; Abuzer Coskun (Emergency Medicine International)
Aim. Acute coronary syndrome (ACS) continues to be the main cause of mortality and morbidity globally. The aim was to assess serum procalcitonin (PCT), mean corpuscular hemoglobin concentration (MCHC) and mean platelet volume (MPV) levels in terms of complications after myocardial infarctus, triple vein coronary artery disease (TVCAD), and mortality prediction. Material and Method. This cross-sectional cohort study included 200 patients with ACS attending the emergency department of our hospital with chest pain and admitted to the cardiology clinic from January 2014 to December 2016. Patients were divided into 4 groups as inferior group, anterior group, NSTEMI group, and UA group according to diagnosis. These groups were compared in terms of complications occurring after MI, TVCAD, and mortality rates. Results. There were significant differences in terms of complications forming after ACS, TVCAD, and mortality. The inferior subgroup had high PCT and MCHC levels and was found to have more complications developing and mortality compared to other groups. Patients with high PCT and MPV values were identified to have higher mortality and TVCAD. In the anterior subgroup, ischemic heart failure was higher compared to the other groups. In the interior, anterior, and non-ST elevated myocardial infarctus (NSTEMI) groups, the 0-, 6-, and 12-hour cTnI values were significantly higher compared to the UA group, while the anterior group had a significantly higher 12-hour cTnI value compared to the NSTEMI group. Correlation analysis for PCT, MCHC, and MPV with complications developing after MI, mortality, and TVCAD found positive and statistically significant correlations. Conclusion. High PCT, MCHC, and MPV levels in acute coronary syndrome may be beneficial predictive values in terms of complications that may develop, TVCAD, and mortality.